KLASIFIKASI TINGKAT KELUARGA SEJAHTERA DENGAN MENGGUNAKAN METODE REGRESI LOGISTIK ORDINAL DAN FUZZY K-NEAREST NEIGHBOR (STUDI KASUS KABUPATEN TEMANGGUNG TAHUN 2013) - Dini Puspita; Suparti Suparti; Yuciana Wilandari (Jurnal Gaussian, 2014)
Indonesian is a country that have a lot of people, its about 250 millions people. Each of they have a family. Family is a group of person who have relationship and responsibility for each other. The characteristic of family is very important in relationship with society. A lot of requirement must to be have in family. Ownership requirement in family can be figure of that family. In case, accuracy of classification about prosperity family in Kabupaten Temanggung 2013th will be analysed, in BKKBN is have 5 level of prosperity family, there are pra prosperity family, prosperity family 1, prosperity family 2, prosperity family 3, and prosperity family 3 plus. Regression Logistics Ordinal method and Fuzzy K-Nearest Neighbor (FK-NN) method be use for analysis this minithesis. From the analysis regression logistics ordinal accuracy of classification have value 80,47%, and FK-NN have value 87,60%. Both of the value accuracy of classification can get conclusion regression logistics ordinal method have a less value than FK-NN. So FK-NN method is a best method for level of prosperity family in Kabupaten Temanggung 2013th.Keywords : Prosperity Family, Regression Logistics Ordinal, Fuzzy K-Nearest Neighbor (FK-NN)